(3OhQ GdGQTGO GdfaSj GdQjGVj aj eNJda eQGMd GdJMVjQ ddefGaSI dOi dGYHj cQI GdbOe s - (3EbQGfGjSj, jhSas; (3Hf Jhej, fUQ GdOjfs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3jJfGhd ehVhY gPg GdOQGSI OhQ GdGQTGO GdfaSj GdQjGVj aj eNJda eQGMd GdJMVjQ ddefGaSI GdQjGVjI (B( (3bHd(B- (3CKfGA hHYO (B) (3hPdc aj GWGQ GHQGR aYGdjI GdYedjI GdGQTGOjI YfO dGYHj cQI GdbOe , hgj OQGSI hUajI dHYV GfOjI GdQGHWI GdLRGFQjI GdeMJQaI GdChdi CcGHQ, hdbO GSJfJLfG ef gPg GdOQGSI Cf ddEQTGO GdfaSj GdQjGVj OhQ aj GdJbdjd ef XGgQI Gdbdb GdPj jJYQV dg dGYHj cQI GdbOe aj eQMdI eG bHd GdefGaSI GdQjGVjI, hCf ddEQTGO GdfaSj GdQjGVj OhQ aj RjGOI bOQI JQcjR GdGfJHGg hPdc CKfGA ELQGA GdefGaSI GdQjGVjI dOi dGYHj cQI GdbOe, ddEQTGO GdfaSj GdQjGVj OhQ aj RjGOI eSJhi GdGSJQNGA aj eQMdI eG HYO GdefGaSI GdQjGVjI dOi dGYHj cQI GdbOe(B.s
(3OcJhQGIs
Keywords: (3GdEQTGO GdfaSj G dQjGVjs; (3GdGQTGO GdfaSj GdQjGVjs; (3GdefGaSI GdQjGVjIs; (3cQI GdbOes